Perfection : coming to terms with being human - Hyde, Michael J., 1950- (Waco, Tex. : Baylor University Press, 2010)
"In a survey of the history of the idea of human perfection, Michael J. Hyde leads an excursion through philosophy, religion, science, and art. He delves into the canon of Western thought, drawing on figures from St. Augustine and John Rawls to Leonardo da Vinci and David Hume to Kenneth Burke and Mary Shelley. On the journey, Hyde expounds on the workings of daily existence, the development of reason, and the bounds of beauty. In the end, he ponders the consequences of the perfection-driven impulse of medical science and considers the implications of the burgeoning rhetoric of "our posthuman future." It is a triumphant examination of the human quest for significance."--BOOK JACKET
Coming to terms with perfection -- God on a good day -- Interpreting the call -- The otherness all around us -- Reason -- Beauty -- The lived body -- The good life, the good death -- The biotechnology debate -- On being an oxymoron
Includes bibliographical references (p. 281-308) index
Keywords: Perfection